2019
DOI: 10.1017/s0031182019001562
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle stages, specific organelles and invasion mechanisms ofEimeriaspecies

Abstract: Apicomplexans, including species of Eimeria, pose a real threat to the health and wellbeing of animals and humans. Eimeria parasites do not infect humans but cause an important economic impact on livestock, in particular on the poultry industry. Despite its high prevalence and financial costs, little is known about the cell biology of these ‘cosmopolitan’ parasites found all over the world. In this review, we discuss different aspects of the life cycle and stages of Eimeria species, focusing on cellular struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 182 publications
(310 reference statements)
2
61
0
2
Order By: Relevance
“…Results correlated with previous findings for some of these proteins: (i) presence of alternative types of surface antigen proteins (SAGs) between sporozoites and merozoites (Tabares et al, 2004 ); (ii) high abundance of microneme (MIC) proteins during invasion (Bumstead and Tomley, 2000 ); and (iii) overexpression of rhoptry (ROP) and dense granule (GRA) proteins during endogenous development (Oakes et al, 2013 ; Xue et al, 2020 ). These data further corroborate the suitability of the in vitro system to mimic endogenous development (Burrell et al, 2020 ) and are an important source of information to design specific interventions for the study of these relevant proteins. The detection by MS of these proteins indicated that they are present at significantly abundant levels to be targeted (e.g., antibody binding, enzymatic cleavage) and evaluated by this in vitro system.…”
Section: Discussionsupporting
confidence: 78%
“…Results correlated with previous findings for some of these proteins: (i) presence of alternative types of surface antigen proteins (SAGs) between sporozoites and merozoites (Tabares et al, 2004 ); (ii) high abundance of microneme (MIC) proteins during invasion (Bumstead and Tomley, 2000 ); and (iii) overexpression of rhoptry (ROP) and dense granule (GRA) proteins during endogenous development (Oakes et al, 2013 ; Xue et al, 2020 ). These data further corroborate the suitability of the in vitro system to mimic endogenous development (Burrell et al, 2020 ) and are an important source of information to design specific interventions for the study of these relevant proteins. The detection by MS of these proteins indicated that they are present at significantly abundant levels to be targeted (e.g., antibody binding, enzymatic cleavage) and evaluated by this in vitro system.…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, the physical presence of dense granule organelles is elusive in Eimeria sporozoites [7]. Dense granules, as defined in T. gondii and other apicomplexans, have not been visualized by electron microscopy of sporozoites of E. tenella [7,91]. Along with a lack of visual evidence of dense granules, there is sparse conservation of genes encoding GRA protein orthologues in Eimeria genomes, as evidenced by the low numbers of T. gondii GRA orthologues found in transcriptomic [92], proteomic (in E. tenella) [93,94], and protein characterization studies [95], where less than 10 proteins have been identified as potential Eimeria GRAs in comparison to the 53 proteins annotated for T. gondii (www.toxodb.org, accessed on 26 August 2021).…”
Section: Coccidian Stages Diverge In Trafficking and Secretion To The Parasitophorous Vacuole (Pv) 41 Dense Granules And Their Role In Thmentioning
confidence: 99%
“…This process is followed by sexual reproduction (gametogony) to form new oocysts. Then, these new oocysts are voided to the environment via the feces, where sporulation (sporogony) takes place [ 7 ]. Similarly, when ingested by felids (definitive host), Toxoplasma oocysts (or tissue cysts) release sporozoites (or bradyzoites) that, after the invasion of host cells, undergo asexual (endopolygeny) and sexual (gametogony) replication in the gut epithelium, producing oocysts that are released to the environment [ 8 ].…”
Section: Coccidian Lifecycles and Endogenous Developmentmentioning
confidence: 99%
See 2 more Smart Citations